Formulasi Minuman Serbuk Instan Jambu Merah (Psidium guajava L.) yang Dikeringkan dengan Metode Foam Mat Drying: The Formulation of Red Guava (Psidium guajava L.) Instant Powder Drink using Foam Mat Drying Method - Nurbaya, Syarifa Ramadhani; Azara, Rima; Prihatiningrum, Andriani Eko; Kinanti, Kintan Sari; Widayanti, Silvi (Amerta Nutrition, 2025)
Background: Red guava juice offers various benefit yet its shelf life is short. Processing red guava juice into powder extends the shelf life of the product. The foaming method or foam mat drying was employed in this research to produce red guava juice powder, using Maltodextrin as the filler, egg white as the foaming agent and sucrose to taste. Objectives: This research examined the physical and chemical characteristics of the red guava instant powder drink to determine the best formulation. Methods: The first step of research was the production guava juice powder with different maltodextrin concentrations (5%, 10%, 15%) and egg white concentrations (3%, 6%, 9%). The formulation of guava juice instant powder drink involved the addition of different sucrose concentrations (10%, 20%, 30%) and guava juice powder to water ratios (1:5, 1:10, 1:15). Physical characteristics were observed, including the bulk density, solubility, color (L, a, b), and viscosity. The chemical characteristics that included total carotene and vitamin C content were also examined. The most optimal treatment from the second step underwent the proximate analysis and sodium content test, which data were analyzed using analysis of variance (ANOVA) and Tukey/HSD test. Results: The use of 15% maltodextrin and 3% egg white showed the most optimal result, and the use of 30% sucrose concentration and 1:5 guava juice powder to water ratio was determined as the best formulation. Conclusions: Red guava instant powder drink is an instant powder drink product that uses natural ingredients. One packet of red guava instant powder drink contains a total of 76 kcal of energy.